DOZ047.21: Esophageal atresia and long-term quality of life in Italian population: a pilot study. (24th June 2019) - Parracciani, M; Tona, C; Gamba, P; Dall'Oglio, L; Conforti, A; Cheli, S
Abstract: Introduction: In Italy, long-term outcomes of esophageal atresia (EA) are poorly understood. The Italian Association 'Family with Esophageal Atresia' (F.AT.E.) and Tages Onlus, and some Italian pediatric centers of reference for AE, collaborated to define the first work about long-term outcomes and quality of life (QoL) in a cohort of Italian adults and young adults born with AE. As a rare disease, given the specificity of the reference population and the absence of similar research, this study was in any case designed to be a pilot study. Methods: To date, 65 adults born with EA have participated in completing the questionnaire. Two survey formats were created: (i) a standard paper questionnaire and (ii) an online platform. The questionnaire included the following tools: (i) socio-personal data; (ii) QoL questionnaire (SF-36); (iii) a sub-battery of short questionnaires to investigate psychological adaptation to chronic diseases (HADS, IES-R, Brief-COPE); (iv) a questionnaire linked to the specific perception of social support (MOS-SSQ); and (v) four open questions developed to investigate the subjective experience of QoL and long-term morbidity. The use of quantitative and qualitative data (Mixed Methods) will allow us to deeply investigate the experience and perceptions related to the QoL. Results: Our results indicated that AE type C is the most frequent, and the renal ones are the most common malformations associated with AE. According to the dysphagia score, more than half are suffering states of dysphagia. A significant negative statistical association emerges between the presence of dysphagia and perception of social support (MOSS-SSS). Gastroesophageal reflux symptoms are reported by more than half, in association with antireflux medications. At last, it emerges that the main psychological factors accused are sleep disorders and obsessive-compulsiveness symptoms. Conclusions: Despite this study confirming that the frequency of respiratory, gastrointestinal, and musculoskeletal symptoms affects the QoL, it appears generally good. The information provided by this study could be an incentive to implement and improve long-term follow-up programs and to involve more specialist adult doctors in the care of these patients.